Factors influencing the occurrence of perineal rupture at BPM Mesrida Simarmata, AmKeb - Srininta, Srininta; Simarmata, Mesrida; Purnamasari, Eka; Br Ginting, Astaria; Sihotang, Dini (Journal of Midwifery and Nursing, 2024)
Perineal rupture is an injury to the perineum that is caused by natural tissue damage due to pressure on the fetal head or shoulders during delivery. To determine the factors that influence the incidence of perineal rupture in mothers giving birth at BPM Mesrida Simarmata, Am Keb in 2022. This type of research is quantitative descriptive with a retrospective approach. The population of this study was pregnant women who experienced perineal rupture in 2022. The total population was 30 people and with a total sampling technique. The instrument uses a checklist and the data analysis technique uses analysis. The majority of respondents had grade 2 perineal rupture. The mother's age was 20-35 years as many as 27 people (90%), the majority of parity were multiparous as many as 18 people (60%). BBL 2500-3500 grams was 26 people (67%) and pregnancy interval > 2 years was 16 (53%). The majority of respondents are in normal condition, it is necessary to investigate things that cause perineal rupture, such as pushing techniques and efforts to make the perineum elastic. The parity of multiparous respondents needs to be researched with the variable history of previous perineal rupture.